2004
DOI: 10.3989/scimar.2004.68n4483
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient diffusive fluxes from sediments in the northern Gulf of Aqaba, Red Sea

Abstract: SUMMARY: Measurements of dissolved inorganic nutrients (NH-2 and SiO 2 ) in pore waters (PW) and overlying bottom waters (OBW) were carried out in sediments of two reefs on the Jordanian coast of the Gulf of Aqaba at different water depths down to 30 m. One of the two sites was a marine reserve in front of the Marine Science Station (MSS) and the other hosted an Industrial Complex Zone (ICZ). The PW samples were retrieved using specially designed interstitial water traps. The concentrations in the OBW were wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Otherwise, in the Ria of Ortigueira the thicker oxic-suboxic sediment layer in spring act as retention to the upward diffusive phosphate flux while at summer this layer is reduced due to the increase of organic matter mineralization rates (Ishikawa and Nishimura, 1989;Falcão et al, 2006). Phosphate and silicate diffusive fluxes were low compared with the fluxes of important river-dominated estuaries (Watson et al, 1993;Mortimer et al, 1999), but similar to those found by Al-Rousan et al (2004) in coral reef along the Jordanian coast of the Gulf of Aqaba.…”
Section: Nutrient Fluxes Between Sediment and Overlying Water At Submsupporting
confidence: 69%
“…Otherwise, in the Ria of Ortigueira the thicker oxic-suboxic sediment layer in spring act as retention to the upward diffusive phosphate flux while at summer this layer is reduced due to the increase of organic matter mineralization rates (Ishikawa and Nishimura, 1989;Falcão et al, 2006). Phosphate and silicate diffusive fluxes were low compared with the fluxes of important river-dominated estuaries (Watson et al, 1993;Mortimer et al, 1999), but similar to those found by Al-Rousan et al (2004) in coral reef along the Jordanian coast of the Gulf of Aqaba.…”
Section: Nutrient Fluxes Between Sediment and Overlying Water At Submsupporting
confidence: 69%
“…Data are mean 6 SE, showing the number of values used in the calculations (n). See Table 2 focusing on specific habitats such as sediments (Capone et al 1992;Rasheed et al 2002;Al-Rousan et al 2004), coral cavities (Gast et al 1998;Scheffers et al 2004;Rasheed et al 2006), or micro atolls (Steven and Atkinson 2003), but the relevance of these habitat-specific rates at the scale of a reef community or ecosystem remains difficult to discern (Table 6). The release rates that were estimated in the present study, by assuming gross nutrient uptake was mass-transfer limited (J 2 MTL ), were on the same order as those documented in coral cavities and micro atolls, but were an order of magnitude higher than observed over carbonate sediments (generally a net sink; Wild et al 2005;Eyre et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…DO concentration may influence nitrification and denitrification, since oxygen penetration into the sediment stimulates the aerobic process of nitrification (Al-Rousan et al 2004). Community respiration during dark incubations may cause depletion in DO at the end of the incubation, especially in summer and autumn, when the DO concentrations are the lowest and the respiration rates the highest.…”
Section: Factors Influencing Seasonal Sediment -Water Fluxesmentioning
confidence: 99%